Razširjenost plazilcev v Sloveniji - Krofel, Miha (Natura Sloveniae, 2009)
In this paper, we present a review of distributional data for reptiles in Slovenia collected prior to April 2009. Data are presented in a 10x10 km UTM grid and divided into two classes by the ageČ 1995 or earlier, and 1996-2009. With this review, we would like to create a basis for future field work and emphasize the distributional gaps. For some species, the knowledge of their distribution has increased substantially in the last 13 years (e.g. for Podarcis muralis, Vipera aspis, Zamenis longissimus, Anguis fragilis, Natrix natrix, N. tessellata, and Lacerta viridis ž bilineata). The increase in some introduced species (e.g. Trachemys scripta and Testudo hermanni) is probably aconsequence of additional introductions by people. On average, the number of UTM squares with recorded presence of autochthonous species has increased by 12% per species after 1995. For some of the species, no more records have beenmade after 1995 in many areas where they had been recorded before (e.g. Podarcis melisellensis, Vipera ammodytes, V. berus, Emys orbicularis, and Lacerta agilis), which might indicate the possibility of local extinctions. For the future, we recommend a continual monitoring of the population trends concerning individual species.
Keywords: plazilci; reptile; Slovenia; Slovenija